Perlindungan Hukum Pidana Penggelapan Atas Harta Kekayaan(Boedel Pailit) Debitur yang Mengakibatkan Kerugian Terhadap Kreditur - Riza Yoga Pramana; Liliana Tedjosaputro (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of the study is to determine and analyze the criminal law protection of embezzlement of assets (Boedel Bankruptcy) of debtors that result in losses to creditors, and obstacles to criminal law enforcement for embezzlement of debtors' assets that result in the formulation of the problem What is the position of criminal law Embezzlement of debtors on their assets that causes creditor losses and how to overcome them. The method used in this study uses the Normative juridical approach method, the data sources are secondary data and primary legal materials. Research Results (1). Legal protection of the criminal act of embezzlement of the debtor that causes losses to the debtor, after being declared bankrupt by a judge is a criminal act of embezzlement regulated by Article 372 of the Criminal Code and Article 400 paragraph (1) of the Criminal Code, because the fulfillment of the criminal elements is fulfilled. (2). Obstacles faced, Uncooperation of the insolvent debtor in carrying out legal proceedings due to the lack of level of legal awareness possessed by the insolvent debtor. To overcome this, the bankrupt debtor should comply with the contents of the decision of the Supreme Court case Number 2K / Pdt.Sus-Pailit / 2019 willing to submit the legality of access to the curator team that will resolve, and as a good Indonesian citizen must obey, submit, and obey the laws and laws in force in Indonesia.